2015
DOI: 10.1097/adm.0000000000000128
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practice of Electronic Cigarette Use Among Pregnant Women

Abstract: Misconceptions about e-cigarettes are common among pregnant women, potentially motivating use that may pose risks to both maternal and child health. Screening and education regarding e-cigarettes should be included in prenatal care. Future research in this area is necessary, including research examining pregnancy outcomes among women who use e-cigarettes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
132
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(148 citation statements)
references
References 31 publications
11
132
1
4
Order By: Relevance
“…There are also complex societal underpinnings to smoking in pregnancy, because teen pregnancy, low income, low education, and living with a smoker are important factors increasing the odds of smoking during pregnancy, with a gradient linking the number of risk factors to the percentage of smoking (28). The estimated number of pregnant smokers is also likely underestimated; studies have shown at least 20% of pregnant smokers lie about their habit (29), which is even more concerning in the context of vapers, who may already believe vaping to be safe during pregnancy (4). Because the major addictive component of cigarette smoke is nicotine, these data strongly imply that at least 50% of vapers will continue to vape while pregnant despite best efforts at cessation (7,8).…”
Section: Effects Of Maternal Smoking During Pregnancy On Lung Developmentioning
confidence: 98%
See 2 more Smart Citations
“…There are also complex societal underpinnings to smoking in pregnancy, because teen pregnancy, low income, low education, and living with a smoker are important factors increasing the odds of smoking during pregnancy, with a gradient linking the number of risk factors to the percentage of smoking (28). The estimated number of pregnant smokers is also likely underestimated; studies have shown at least 20% of pregnant smokers lie about their habit (29), which is even more concerning in the context of vapers, who may already believe vaping to be safe during pregnancy (4). Because the major addictive component of cigarette smoke is nicotine, these data strongly imply that at least 50% of vapers will continue to vape while pregnant despite best efforts at cessation (7,8).…”
Section: Effects Of Maternal Smoking During Pregnancy On Lung Developmentioning
confidence: 98%
“…The combination of the addictive nature of nicotine with the perception of relative safety suggests that e-cigarette use during pregnancy will likely increase (4). Although nicotine replacement therapy has been used during pregnancy (5,6), on the basis that nicotine alone will be safer than conventional cigarette use, the potential continued use of e-cigarettes by e-cigarette-only users during pregnancy raises heightened safety concerns of e-cigarette use during pregnancy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, three small-scale studies have examined lay perceptions of the safety of ecigarette use during pregnancy (Baeza-Loya et al, 2014;Fallin, Miller, Assef, & Ashford, 2016;Kahr et al, 2015;Mark et al, 2015). These studies have found that participants (many of whom were pregnant) viewed e-cigarette use during pregnancy as less harmful than smoking.…”
Section: Introductionmentioning
confidence: 99%
“…A survey conducted in the USA with 316 pregnant women reported that 13% of women had ever used an e-cigarette and only two women were using e-cigarettes daily; ever-users were typically older and current smokers (Mark, Farquhar, Chisolm, Coleman-Cowger, & Terplan, 2015). Evidence regarding the efficacy of e-cigarettes as a cessation device for pregnant women is absent, because trials typically exclude pregnant women (Bryce & Robson, 2015).…”
Section: Introductionmentioning
confidence: 99%